A Systematic Assessment of Budgeting and Budgetary Management system of South Sudan: The Case of the Ministry of Finance and Economic Planning - Tieng, Matur (Technium Social Sciences Journal, 2023)
The purpose of this study was to assess the budgetary management system by the Ministry of Finance and Economic Planning to manage the budget effectively and efficiently to meet the financial objective of the government of South Sudan. The study undertook a critical review of all financial policy documents including the appropriation bills, the Public Financial Management and Accountability Act 2011, and other assessment reports conducted by the other individuals and institutions on the financial management system of the government of South Sudan. A self-administered questionnaire was used to collect first-hand information from the spending agencies of the government about how the budget is being managed on their behalf. And to find out whether the current budget management system meets the expectations of the spending agencies. Among the major trending issues found during this study were lack of transparency in the budget management, lack of inclusive participation of all stakeholders in the budget planning, weak internal and external control mechanism, lack of qualified staff in the accounts and budget departments, lack of timely and adequate budgetary information sharing, and failure of the parliament to exercise its oversight role on the planning and implementation of the budget, among others. The study concluded that significant reform in the financial management system in South Sudan is needed, as well as the deployment of qualified accountants to all spending agencies. This will ensure proper budget discipline among all spending agencies since the qualified workforce is at the driving will of the financial system. The Treasury Single Account be implemented without any objection by some spending agencies such as the security sector. And the custodian of the system be the Central Bank of South Sudan since it is the fiscal agent of the government.